Outcome of lamivudine resistant hepatitis B virus infection in the liver transplant recipient. Issue 1 (1st January 2000) - Mutimer, D; Pillay, D; Shields, P; Cane, P; Ratcliffe, D; Martin, B; Buchan, S; Boxall, L; O'Donnell, K; Shaw, J; Hübscher, S; Elias, E
Abstract : BACKGROUND: In many transplant centres lamivudine is an important component of prophylaxis against, and treatment of, hepatitis B virus (HBV) graft infection. Drug resistant HBV species with specific polymerase mutations may emerge during lamivudine treatment. AIMS: To examine the clinical consequences of graft infection by lamivudine resistant virus. METHODS: The clinical course of four liver transplant patients who developed graft infection with lamivudine resistant virus was reviewed. The response of HBV infection to reduction of immunosuppression and to manipulation of antiviral therapy was assessed. For each patient, serum viral titre was measured and the viral polymerase gene was sequenced at multiple time points. RESULTS: High serum titres were observed following emergence of the lamivudine resistant species. Wild type HBV re-emerged as the dominant serum species after lamivudine withdrawal. All patients developed liver failure, and onset of liver dysfunction was observed when resistant virus was the dominant serum species. In three patients, liver recovery was observed when immunosuppression was stopped and when alternative antivirals were given. Wild type virus appeared to respond to ganciclovir, and to reintroduction of lamivudine. For one patient, introduction of famciclovir was associated with clinical, virological, and histological response. CONCLUSIONS: Failure of lamivudine prophylaxis may identify patients at special risk for the development of severe graft infection. Treatment of graft reinfection should include reduction of immunosuppression, and systematic exposure to alternative antivirals. Viral quantitation and genetic sequencing are essential components of therapeutic monitoring.